Sistema Web Blended Learnig en el aprendizaje de una lengua extranjera en la ESPAM MFL. - Álava Cagua, Nathaly Valeria (2018)
The purpose of this research was to develop a web system for the ESPAM MFL Language Center that promotes autonomous learning of a foreign language. The methodology used in the development of the system was XP: in the planning phase the system requirements were established with the collaboration of the Language Center, in the design phase user interfaces design were created using the Bootstrap Framework and JavaScript, in the develop phase the system was developed using C #, JavaScript, Ajax language and HTML5 and in the testing phase the white box and black box tests were used for the verification of the system. Finally, an inferential study was carried out to validate the usefulness of the system, which was carried out in the last week of November of 2017 with two groups of first level of Language Center; one used the system and the other did not. Later, a questionnaire was applied to make a comparison of means between both groups using the t test of independent samples. According to the results of the test, no significant evidence was found to show that the system encourages autonomous work, however, it was found that there is a difference in the level of learning in listening, reading, grammar/vocabulary, and speaking skills with p value 0.002, 0.044, 0.022, 0.013 respectively in favor the group that used the system.